Evaluating the performance of ACR, SLICC and EULAR/ACR classification criteria in childhood onset systemic lupus erythematosus - Reem Abdwani; Eiman Masroori; Eiman Abdullah; Safiya Al Abrawi; Ibrahim Al-Zakwani (BMC, 2021)
Abstract Background The ACR 1997, SLICC 2012 and EULAR/ACR 2019 classification criteria were validated based on adult patients. To date, there are no classification criteria specific for children with SLE. The aim of the study is to compare the performance characteristics among the three SLE classification criteria (ACR-1997, SLICC-2012 and EULAR/ACR-2019) in childhood onset SLE (cSLE) cohort of Arab ethnicity from Oman. Methods We conducted a retrospective multicenter study in Oman of cSLE patients as cases and patients with other rheumatic disease with a positive ANA titer as controls. The cSLE cases recruited were children diagnosed with SLE before 13 years of age. Data was retrospectively collected to establish the ACR-1997, SLICC-2012 and EULAR/ACR-2019 criteria fulfilled at first visit, first year follow up and last follow up. Results Study population included 113 cSLE cases (mean age at diagnosis of 7.3 ± 3.4 years with disease duration of 6.1 ± 4.6 years) and 51 controls (mean age at diagnosis 5.0 ± 3.4 with disease duration 5.7 ± 3.9). The cSLE cases had higher frequency of familial SLE than controls (38% vs 7.8%; p < 0.001). The performance measures demonstrated that EULAR/ACR-2019 criteria had the highest sensitivity (81, 88, 89%) compared to ACR 1997 (49, 57, 66%) and SLICC 2012 (76, 84,86%); while the ACR 1997 had the highest specificity (96%) compared to SLICC 2012 (94%) and EULAR/ACR 2019 (90%) at first visit, first year and last assessment. When we increased the threshold score to ≥13 rather than the traditional score ≥ 10 for ACR/EULAR 2019, there was increased specificity (96%) at the expense of lower sensitivity (76, 83, and 84%) at first visit, first year and last assessment. Conclusion In this cSLE population, EULAR/ACR 2019 scored better at initial presentation, first year and last assessment follow up. Further multinational studies are needed to validate the appropriate cut off score for the newly proposed ACR/EULAR 2019 classification criteria in cSLE to increase early sensitivity and specificity for cSLE classification.